Fragment‐Based Discovery of 5‐Arylisatin‐Based Inhibitors of Matrix Metalloproteinases 2 and 13. (15th July 2016) - Agamennone, Mariangela; Belov, Dmitry S.; Laghezza, Antonio; Ivanov, Vladimir N.; Novoselov, Anton M.; Andreev, Ivan A.; Ratmanova, Nina K.; Altieri, Andrea; Tortorella, Paolo; Kurkin, Alexander V.
Abstract: Matrix metalloproteinases (MMPs) are well‐established targets for several pathologies. In particular, MMP‐2 and MMP‐13 play a prominent role in cancer progression. In this study, a structure‐based screening campaign was applied to prioritize metalloproteinase‐oriented fragments. This computational model was applied to a representative fragment set from the publically available EDASA Scientific compound library. These fragments were prioritized, and the top‐ranking hits were tested in a biological assay to validate the model. Two scaffolds showed consistent activity in the assay, and the isatin‐based compounds were the most interesting. These latter fragments have significant potential as tools for the design and realization of novel MMP inhibitors. In addition to their micromolar activity, the chemical synthesis affords flexible and creative access to their analogues. Abstract : Isatins identified : Matrix metalloproteinases (MMP)‐2 and 13 are well‐established targets for cancer treatment, and many MMP inhibitors have been developed. However, most of them have shown side effects during clinical trials. In this work, novel putative non‐zinc‐binding MMP chemotypes were identified by screening a small fragment‐based library.